Whole-body Mass Spectrometry Imaging by Infrared Matrix-assisted Laser Desorption Electrospray Ionization (IR-MALDESI) - Nazari, Milad (J Vis Exp, 2016)
Ambient ionization sources for mass spectrometry (MS) have been the subject of much interest in the past decade. Matrix-assisted laser desorption electrospray ionization (MALDESI) is an example of such methods, where features of matrix-assisted laser desorption/ionization (MALDI) (e.g., pulsed nature of desorption) and electrospray ionization (ESI) (e.g., soft-ionization) are combined. One of the major advantages of MALDESI is its inherent versatility. In MALDESI experiments, an ultraviolet (UV) or infrared (IR) laser can be used to resonantly excite an endogenous or exogenous matrix. The choice of matrix is not analyte dependent, and depends solely on the laser wavelength used for excitation. In IR-MALDESI experiments, a thin layer of ice is deposited on the sample surface as an energy-absorbing matrix. The IR-MALDESI source geometry has been optimized using statistical design of experiments (DOE) for analysis of liquid samples as well as biological tissue specimens. Furthermore, a robust IR-MALDESI imaging source has been developed, where a tunable mid-IR laser is synchronized with a computer controlled XY translational stage and a high resolving power mass spectrometer. A custom graphical user interface (GUI) allows user selection of the repetition rate of the laser, number of shots per voxel, step-size of the sample stage, and the delay between the desorption and scan events for the source. IR-MALDESI has been used in variety of applications such as forensic analysis of fibers and dyes and MSI of biological tissue sections. Distribution of different analytes ranging from endogenous metabolites to exogenous xenobiotics within tissue sections can be measured and quantified using this technique. The protocol presented in this manuscript describes major steps necessary for IR-MALDESI MSI of whole-body tissue sections.